Efecto del extracto hidroalcohólico de la raíz de lepidium meyenii (ecotipo rojo y negro), sobre citología vaginal y peso uterino en rattus norvegicus var albinus ooforectomizadas expuestas a gran altura - Burgos Velarde, Jesús María (2012)
This research is based on determining the effect of hydroalcoholic extract of the root of Lepidium meyenii "maca" (ecotype red and black) on vaginal cytology and uterine weight in Rattus norvegicus var albinus ooforectomized exposed to 3850 m. We conducted a randomized into five groups of 6 specimens each (White, Control, Pattern, Problem I and Problem II), ooforectomized previously except the White group. Then administered at doses of hydroalcoholic extract of maca 1.5g/Kg/day black and red, group Problem I and II respectively, the Pattern group was administered estrogen at a dose of 200  g / kg / day. Were treated at sea level with this procedure for 28 days, and then were exposed to 3850 m. for a period of 31 days. After this procedure the specimens were sacrificed, obtaining data for vaginal cytology and uterine weight, which was used for analysis of variance (ANOVA). We found an increased level estrogenic effect vaginal cytology by red ecotype Lepidium meyenii, while a greater effect on uterine weight gain by black ecotype of Lepidium meyenii.